2021
DOI: 10.3390/nano11113106
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Magnetic Nanomaterials in Agricultural Applications

Abstract: The development of functional nanomaterials exhibiting cost-effectiveness, biocompatibility and biodegradability in the form of nanoadditives, nanofertilizers, nanosensors, nanopesticides and herbicides, etc., has attracted considerable attention in the field of agriculture. Such nanomaterials have demonstrated the ability to increase crop production, enable the efficient and targeted delivery of agrochemicals and nutrients, enhance plant resistance to various stress factors and act as nanosensors for the dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 243 publications
(225 reference statements)
0
10
0
Order By: Relevance
“…Nanotechnology has a wide range of potential applications, which will revolutionize the fields of science and technology in the 21st century, including in the sectors of materials science, biomedicine, agriculture, and industry, and will play important roles in various changing fields [ 4 ]. The application of nanotechnology to plant science and agriculture is one of the fastest-growing areas of nanoresearch [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. In agriculture, nanoparticles are mainly used to effectively deliver exogenous insecticidal factors to improve plant health, expand the insecticidal spectrum, reduce pesticide use, prolong the period of efficacy, and reduce environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Nanotechnology has a wide range of potential applications, which will revolutionize the fields of science and technology in the 21st century, including in the sectors of materials science, biomedicine, agriculture, and industry, and will play important roles in various changing fields [ 4 ]. The application of nanotechnology to plant science and agriculture is one of the fastest-growing areas of nanoresearch [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. In agriculture, nanoparticles are mainly used to effectively deliver exogenous insecticidal factors to improve plant health, expand the insecticidal spectrum, reduce pesticide use, prolong the period of efficacy, and reduce environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Nanotechnology allows to achieve a diverse range of objectives, including but not limited to higher solubility of active ingredients (AIs), slower release, improved delivery efficiency, and better bioactivity. These versatile characteristics make them well-suited for a wide range of applications. In recent years, there has been a growing interest among scientists in utilizing nanoparticles for the development of environmentally friendly pesticides, and the construction of nanosized pesticides and plant elicitors is developing fast in recent years. These novel nanopesticides can achieve several advantages, such as better stability, controlled/smart release, targeted delivery, and higher control efficacy. Wang et al found that the overall efficacy of nanopesticides against target pests was increased by 31.5%, with an 18.9% increased efficacy in field trials when compared with non-nanoscale pesticides. Importantly, the higher utilization rate of nanopesticides is beneficial for reducing the application of AIs, alleviating the negative effects on environment and human health. Consequently, exploring efficient nanocarriers for the effective utilization of pesticides in agricultural production is a key aspect of plant protection research.…”
Section: Introductionmentioning
confidence: 99%
“…It can be an efficient and eco-friendly alternative to agrochemicals that promote regenerative agriculture, integrated with the approach associated with One Health. Bionanotechnology could be applied in agriculture, remediation, water treatment, pest detection, and control, for example, developing porous nano zeolites capable of absorbing water or soil chemical contaminants [ 11 ]; nanocapsules capable of releasing the necessary pesticide concentration on demand [ 12 ] nanomembranes that control the release of water, fertilizers, and herbicides and serve as water purifiers [ 13 , 14 ]; nanosensors capable of monitoring soil and plants and detecting contaminants and pests [ 15 , 16 ]; magnetic nanoparticles as an agent to combat soil contaminants [ 17 ]; among other applications.…”
Section: Introductionmentioning
confidence: 99%